Lodging forms along life cycles: a comparative view across the Europe - Mauritti, R (Full Papers of the 9th Conference of the European Sociological Association, 2009)
Housing is one of the key dimensions of an individual’s material position and quality of life. In the dominant ideas on the "family" and “family living”, the unit of accommodation emerges as a key descriptive, from which we represent all the social imagery that is - to override itself as fact - the social reality of those elements. In the social perceptions connection to a residence or a "home" or "having a home" determines the very possibility of intimacy and private life - at least in it’s more permanent or durable form in time. Usually the idea of household includes three different dimensions: the household structures: household size and composition; the household relationships: means the different kinds of interaction among household members; and the Kinship: this dimension goes beyond the bond of co-residence, and refers to how often the different groups of relatives and also friends are in touch, help each other, draw up and pursue common strategies to preserve their emotional ties, economic resources, power and prestige. In my presentation I intend to develop a comparative perspective on a European scale, looking at the changes observed in these dimensions simultaneously, and ascertaining how they interact with cultural differences, social and economic conditions and institutional contexts. Social recomposition is a fundamental element of these processes of change. It includes very important aspects of recomposition from the geographical and age-group points of view: longer life spans, alterations in the relative weight of the various age brackets, urbanisation, and national and international mobility and migration. It also includes the profound and comprehensive educational, occupational, socio-economic and socio-cultural recomposition that is taking place, with great intensity, in the different European countries and in the EU as a whole.